Epstein-Barr virus-associated smooth muscle tumor involving the spine of an HIV-infected patient: Case report and review of the literature. (June 2018) - Ehresman, Jeffrey S.; Ahmed, A. Karim; Palsgrove, Doreen N.; Pennington, Zachary; Goodwin, C. Rory; Sciubba, Daniel M.
Highlights: There is no standard of care for EBV-associated smooth muscle tumors. Surgical resection is often warranted to relieve neurologic symptoms. HAART is used to minimize risk of opportunistic infection, the main cause of mortality. There is no consensus whether radiation therapy improves survival in these patients. The pathogenesis of EBV-associated smooth muscle tumors is currently unknown. Abstract: Within the last two decades, there have been multiple reports of Epstein-Barr virus (EBV)-associated smooth muscle tumors in immunocompromised patients. This includes HIV-infected patients, post-transplant patients, and patients with congenital defects of their immune systems. Here we report the case of a 24-year-old African American female with congenital HIV presenting with progressive lower extremity weakness, constipation, aching pain in her shoulders, and subcostal anesthesia. Magnetic resonance imaging (MRI) revealed a large circumferential lesion extending from T1-T3 and a smaller left paraspinal lesion at C6-C7. The T1-T3 mass was excised via a right-sided costotransversectomy with laminectomy and fusion from T1-T3. Highly active antiretroviral therapy (HAART) was started postoperatively, and adjuvant radiotherapy was initiated but patient was lost to follow-up. Surgical pathology demonstrated a smooth muscle tumor diffuse nuclear positivity for EBV-encoded small RNA 1 by in situ hybridization. Although eight studies have reported HIV patients with EBV-associated smooth muscle tumors of the spine, to the author's knowledge, this is the first review comprised solely of patients with spinal involvement with the addition of our patient case.